2013
DOI: 10.1123/smej.7.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Students Beyond Just the Experience: Integrating Reflection Learning into Sport Event Management

Abstract: Sport management as an academic discipline requires a balance of theory and practice through endowing students with knowledge, critical thinking skills, and expertise (Cuneen & Parks, 1997). Professionals call for students being “prepared” for the demands of the sport industry through the acquisition of a quality education and a significant amount of hands-on experience before entering the work force. Researchers have recommended utilizing experiential pedagogical strategies to not only provide the hands-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…study abroad) (Shames & Alden, 2005;Younes & Asay, 2003). Experiential learning and metadiscrete experiential learning models have been extensively researched as effective methods of sport management education (Bruening, Madsen, Evanovich, & Fuller, 2010;Hardin, Bemiller, & Pate, 2013;Irwin, Hays & Irwin, 2011;McKelvey & Southall, 2008;Pauline, 2013;Pauline & Pauline, 2008;Pierce, & Petersen, 2010;Southall, Nagel, LeGrande, & Han, 2003;Spence, Hess, McDonald, & Sheehan, 2009;Walker & Lim, 2007), but there is a lack of literature applying the theory to education through athletics.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…study abroad) (Shames & Alden, 2005;Younes & Asay, 2003). Experiential learning and metadiscrete experiential learning models have been extensively researched as effective methods of sport management education (Bruening, Madsen, Evanovich, & Fuller, 2010;Hardin, Bemiller, & Pate, 2013;Irwin, Hays & Irwin, 2011;McKelvey & Southall, 2008;Pauline, 2013;Pauline & Pauline, 2008;Pierce, & Petersen, 2010;Southall, Nagel, LeGrande, & Han, 2003;Spence, Hess, McDonald, & Sheehan, 2009;Walker & Lim, 2007), but there is a lack of literature applying the theory to education through athletics.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…While some sport management educators have moved towards a more experiential, applied learning model within sport management classrooms, the extent to which academics across the field of sport management are applying these same techniques is unclear. And while a handful of sport management scholars have examined experiential learning outcomes within individual classroom environments (Irwin, Sutton, & McCarty, 2007;Pauline, 2013;Southall, Nagel, LeGrande, and Han, 2003), a singular study has yet to provide an in-depth analysis of the widespread application of experiential learning practices across the field of sport management. In addition, no studies have examined sport management faculty attitudes towards the use of experiential learning practices and their impact on student learning.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…It is evident through published scholarship that some scholars in the field of sport management have been applying Kolb's model of experiential learning theory to their classrooms (Bower, 2013;Miller, Meaney, & Podlug, 2012;Pauline, 2013;Turesky and Gallagher, 2011) in recent years. For example, through her semester long event management course, Pauline (2013) found that Students developed the ability to progress from "noticing" or "making sense" to "making meaning" from their experiences" and that "once the students learned the structure of the course, course content, and got immersed with the event, the reflection process was an eye opening experience for the students to learn about themselves and the course material in a different perspective (p. 10).…”
Section: Theoretical Framework: Experiential Learning Theorymentioning
confidence: 99%
See 2 more Smart Citations